2016
DOI: 10.5194/esurf-4-607-2016
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the sensitivity on a soil area-slope-grading relationship to changes in process parameters using a pedogenesis model

Abstract: Abstract. This paper generalises the physical dependence of the relationship between contributing area, local slope, and the surface soil grading using a pedogenesis model and allows an exploration of soilscape selforganisation. A parametric study was carried out using different parent materials, erosion, and weathering mechanisms. These simulations confirmed the generality of the area-slope-d 50 relationship. The relationship is also true for other statistics of soil grading (e.g. d 10 ,d 90 ) and robust for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…For clarity, and in line with how the choice is presented within the graphical user interface of the model, we henceforth consider this choice in the same way as a parameter. The sediment transport formulae employed for SED were from Einstein (derived for sand-bed rivers) (Einstein, 1950) and Wilcock and Crowe (formulated on sediment ranges between 0.5 and 64 mm) (Wilcock and Crowe, 2003). These were not selected as representing the best fit for the catchments simulated but because they are the formulae available in the unmodified version of CAESAR-Lisflood.…”
Section: User-defined Parametersmentioning
confidence: 99%
“…For clarity, and in line with how the choice is presented within the graphical user interface of the model, we henceforth consider this choice in the same way as a parameter. The sediment transport formulae employed for SED were from Einstein (derived for sand-bed rivers) (Einstein, 1950) and Wilcock and Crowe (formulated on sediment ranges between 0.5 and 64 mm) (Wilcock and Crowe, 2003). These were not selected as representing the best fit for the catchments simulated but because they are the formulae available in the unmodified version of CAESAR-Lisflood.…”
Section: User-defined Parametersmentioning
confidence: 99%
“…increasingly complex processes such as pedogenesis (Vanwalleghem et al, 2013;Welivitiya et al, 2016) and periglacial processes (Andersen et al, 2015;Egholm et al, 2015). Other processes are now being handled in more detail such as hydrodynamic flow models and aeolian processes (Adams et al, 2017;Liu and Coulthard, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Extending the mARM model, Cohen et al (2010) developed mARM3D, which can model soil profile particle-size distribution at a large spatial extent. The SSSPAM (Welivitiya et al, 2016) generalized the formulation of mARM3D and extended the previous research to test more general conditions. Other models such as MILESD (Vanwalleghem et al, 2013) and LORICA (Temme & Vanwalleghem, 2016) incorporated various chemical and biological processes in the simulation.…”
Section: Mechanistic Pedological Models In Dsmmentioning
confidence: 98%
“…Researchers have found that there are strong links between the soils and geomorphology of the landform where they occur (Welivitiya et al, 2016). Landscape evolution models try to model soil development as governed by weathering, erosion or deposition.…”
Section: Mechanistic Pedological Models In Dsmmentioning
confidence: 99%